African scholars and intellectuals in North American academies : reflections on exile and migration - Abidde, Sabella Ogbobode, 1962- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book examines the process and events surrounding the migration of African scholars, as well as their lives and lived experiences within and outside of their colleges and universities. The chapters chronicle the lived-experiences and observations of African scholars in North America and examine a range of issues, ideas, and phenomenon within North American colleges and universities. The contributors examine the political, ethnic, or religious upheavals that informed their migration or banishment; contrast the teaching-learning-research environment in Africa and North America and discuss on and off-campus experience with segregation and racial inequality. This book will be of interest to student and scholars of the African Diaspora, migration and African Studies"--
PART 1. THE PRIVATE SOJOURNS -- African scholars and the question of exile -- My (South African) American story / Stephen Clingman -- Reflections on exile: The case of Ethiopians / Getachew Metaferia -- Understanding the relevance of cultural competence towards African scholars in American academy: Personal experiences / Fraternel Amuri Misako -- In search of knowledge in North America: Challenges and possibilities / Balla Keita -- PART 2. PROCESSES AND PROCEDURES -- Despite the odds: An African woman's experience of navigating the US academy -- Tenure, promotion, and recognition: Challenges of race, ethnicity and gender -- Going with the flow: The unplanned journey in a predominantly white institution -- Boundaries of exclusion and inclusion: Africans and the Western academy -- PART 3. IDENTITY, HOPE, AND ASPIRATIONS -- Post independence African scholars and the second liberation struggle -- On scholarship and the hyphenated African identity adaugo -- The fallacy of unity between Africans and the African Americans -- The invisible minority: Accented speaker and upward mobility in the workplace.
OCLC-licensed vendor bibliographic record.
Keywords: African diaspora; Exile (Punishment) -- Africa; Brain drain -- Africa; Linguistic minorities -- Education -- Social aspects; Discrimination in higher education; Blacks -- Race identity; Africa -- Emigration and immigration; SOCIAL SCIENCE / Emigration & Immigration